Conception and Evaluation of Internet of Things Connecting to RFID Framework - Hajri, M. El Harrak; Asselman, A; Chkouri, M. Yassin (Transactions on Engineering and Computing Sciences, 2017)
The notion of the Internet of the Objects designates a network of objects connected to each other and communicating automatically. In this paper we develop the notions of semantics are becoming increasingly important because, more than ever, they appear as a solution to problems of interoperability and interpretation of data and services by machines. The diversity of possible applications at the intersection of the Internet of Things and the Semantic Web has prompted many research teams to work at the interface between these two disciplines. We wish in this paper to make an inventory of their proposals. We also seek to contribute to the evolution of this field of research by proposing an ontology to describe networks of connected objects. Keywords: Ontologies, Internet of Objects, Interoperability, Data Enrichment.